2012
DOI: 10.7860/jcdr.2012.4370.2298
|View full text |Cite
|
Sign up to set email alerts
|

The ABO Blood Group Distribution and Pulmonary Tuberculosis

Abstract: Aim: Over the years, large number of studies have examined the possible relationship between the blood group type and infection. The present study was aimed at observing the pattern of the ABO blood group distribution among the pulmonary tuberculosis patients from the Andhra region of the Andhra Pradesh state, India. Methods:The ABO blood grouping and Rhesus typing were performed by using the standard slide agglutination reaction in 100 patients with a clinical and a radiological evidence of pulmonary tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
3
6
0
Order By: Relevance
“…Similarly, blood groups and PT correlation studies are also available [4,17,18]. In a study by Rao et al, the authors reported significant association between A blood group and PT; the authors reported that among PT cases 18% PT patients were A+ and non of the participants were A- [17]. Whereas in this study, 2.2% participants were A+ and 0.45% were A-; statistically there was no significant difference (Table 2).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Similarly, blood groups and PT correlation studies are also available [4,17,18]. In a study by Rao et al, the authors reported significant association between A blood group and PT; the authors reported that among PT cases 18% PT patients were A+ and non of the participants were A- [17]. Whereas in this study, 2.2% participants were A+ and 0.45% were A-; statistically there was no significant difference (Table 2).…”
Section: Discussionmentioning
confidence: 50%
“…Viskum K., reported a significant increase in persons with blood groups O and AB [19]. Whereas Rao et al found significant association between PT and persons of blood groups O and A [17]. In this report, in the test group, 3.6% patients were O + and 1.4% were O -; statistically there was no significant difference (Table 2), and 1.1% patients were AB + and 0.45% were AB -; statistically there was no significant difference.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Viskum [12] reported a significant increase of PTB in persons with blood groups O and AB. Rao et al [13] found an association between PTB with persons of blood groups O and A. Gondaliya et al [14] showed significant association among persons with blood group AB and PTB. Preponderance of blood group B was reported among Punjabis [15] and Bengalis.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports indicating that Rh negative persons are more susceptible to TB than Rh positive people. [20] However, Rao et al [13] observed a significant association between the incidence of TB and a positive Rh antigen in blood group A. Lewis and Woods [21] and Shenoy and Daftary [9] have failed to confirm these observations.…”
Section: Discussionmentioning
confidence: 99%